1998
DOI: 10.1088/0957-0233/9/12/003
|View full text |Cite
|
Sign up to set email alerts
|

A thin film coating for phosphor thermography

Abstract: Phosphor thermography is a laser-induced fluorescence method utilized for the temperature sensing of rotating components within inhospitable environments. Results presented here show that thin film coatings for thermographic sensors have a much higher durability than conventional thick film coatings. Room-temperature measurements demonstrate that the intensity of the luminescent emission from thin films is equivalent to that from thick films. Lifetime measurements carried out at C show that thin films survived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 5 publications
3
18
0
Order By: Relevance
“…Other works on other phosphors have also shown an influence of annealing or deposition temperature on the luminescence properties. For example, in Ranson et al 1998, where the effects of annealing temperature and duration are investigated, the researchers showed that similar levels of luminescence between radio frequency (RF) magnetron sputtered Y 2 O 3 :Eu thin films and thick sprayed films can be obtained by altering the annealing parameters. In Choy et al 2011, emission-line sharpening and shift effects were observed to various extents at different deposition temperatures for electronassisted chemical vapour deposition (EACVD) Y 2 O 3 :Eu films.…”
Section: Influence Of the Annealing Duration On The Coating Charactermentioning
confidence: 99%
“…Other works on other phosphors have also shown an influence of annealing or deposition temperature on the luminescence properties. For example, in Ranson et al 1998, where the effects of annealing temperature and duration are investigated, the researchers showed that similar levels of luminescence between radio frequency (RF) magnetron sputtered Y 2 O 3 :Eu thin films and thick sprayed films can be obtained by altering the annealing parameters. In Choy et al 2011, emission-line sharpening and shift effects were observed to various extents at different deposition temperatures for electronassisted chemical vapour deposition (EACVD) Y 2 O 3 :Eu films.…”
Section: Influence Of the Annealing Duration On The Coating Charactermentioning
confidence: 99%
“…This is attributed to their accurate sensing capability over a wide range of temperatures, as well as their ability to withstand a harsh environment. For example, europium doped yttrium oxide (Y 2 O 3 : Eu) has been utilised for high temperature sensing within a rotating gas turbine [1,2] and magnesium fluorogermanate doped with manganese (Mg 4 (F)GeO 6 : Mn) has been explored for thermal mapping of hot spots on the walls of a cryogenic fuel tank [3] . Problems associated with temperature monitoring within a magnetic resonance imaging (MRI)…”
Section: Introductionmentioning
confidence: 99%
“…This was in agreement with tests conducted in Refs. [20][21][22]. There were no observable irreversible effects using powdered samples, and it is envisaged that the results from this investigation would be similar to those produced by vapour deposition or plasma splaying methodologies.…”
Section: Radiometric Photometricmentioning
confidence: 64%